Principales causas de la mortalidad infantil intrahospitalaria. Estudio realizado en Necropsias. 1969 - 1978 - Rozas Llerena, Rubén (1992)
734 intrahospital autopsies of children less than one year old were under research during the 1969-1978 period. The rate average mortality was 44,86 per thousand. The postneonatal component at the end of the last decade decreassed slightly. The premature neonatal component was the mos frequent cause of mortality followed by the neonatal and the late component. The primary causes of mortality in the neonatal period were lung infections (pneumonía), infection of the alimentary tract (enterocolitis), bran haemorrhage, diffuse pulmonary haemorrhage and hialine membrane in that order. In the postneonatal period, the primary causes of mortality were infections of the alimentary tract (enterocolitis) malnutrition, meningoencephalitis, lung infection (pneumonía) and brain haemorrhage.